1995
DOI: 10.1007/bf02790137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium supplementation on thyroid hormone metabolism in phenylketonuria subjects on a phenylalanine restricted diet

Abstract: Type I 5'-deiodinase was recently characterized as a selenocysteine-containing enzyme in humans and other mammals. Up to now, the effect of selenium (Se) supplementation on thyroid hormone metabolism in humans has only been reported in the very peculiar nutritional environment of Central Africa, where combined severe iodine and Se deficiency occurs. In this study, a group of phenylketonuria subjects with a low selenium status, but a normal iodine intake were supplemented with selenium to investigate changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Selenium is a component of multiple deiodinases and thioredoxin reductases (reviewed by Beckett and Arthur, 2005;Kohrle et al, 2005), which highlights the importance of Se in thyroid hormone metabolism. Supplementing Se-deficient animals or humans with additional Se results in improved T 3 status (Beckett et al, 1993;Calomme et al, 1995;Hawkes and Keim, 2003). Awadeh et al (1998) reported that dietary concentration of Se (organically bound and inorganic) of cattle in Se-marginal areas resulted in improved T 3 status of dams and calves.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium is a component of multiple deiodinases and thioredoxin reductases (reviewed by Beckett and Arthur, 2005;Kohrle et al, 2005), which highlights the importance of Se in thyroid hormone metabolism. Supplementing Se-deficient animals or humans with additional Se results in improved T 3 status (Beckett et al, 1993;Calomme et al, 1995;Hawkes and Keim, 2003). Awadeh et al (1998) reported that dietary concentration of Se (organically bound and inorganic) of cattle in Se-marginal areas resulted in improved T 3 status of dams and calves.…”
Section: Discussionmentioning
confidence: 99%
“…Brain D2 activity was decreased in these animals, but this was attributed to the down-regulating effects of the elevated circulating T 4 level (23,24), rather than to a direct effect of Se deficiency (22,25). For example, the plasma T 3 /T 4 ratio is low in individuals prone to Se deficiency, such as the elderly (28), patients with phenylkenouria (29), and cystic fibrosis (30), and it normalizes upon Se supplementation (31). The impact of Se status on various clinical parameters is currently being investigated.…”
mentioning
confidence: 98%
“…Because of protein restrictions in their diet, these patients have an extremely low Se intake, which can influence thyroid hormone metabolism (11)(12)(13)(14)(15)(16). Selenium intake is moderate in Poland, and a tendency toward time-decreasing blood Se levels in children was observed (17).…”
mentioning
confidence: 99%